Biomechanical analysis of the fixation systems for anterior column and posterior hemi-transverse acetabular fractures - Jianyin Lei; Pengfei Dong; Zhiqiang Li; Feng Zhu; Zhihua Wang; Xianhua Cai (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to evaluate the biomechanical properties of common fixation systems for complex acetabular fractures. Methods: A finite element (FE) pelvic model with anterior column and posterior hemi-transverse acetabular fractures was created. Three common fixation systems were used to fix the posterior wall acetabular fractures: 1. Anterior column plate combined with posterior column screws (group I), 2. Anterior column plate combined with quadrilateral area screws (group II) and 3. Double-column plates (group III). And 600 N, representing the body weight, was loaded on the upper surface of the sacrum to simulate the double-limb stance. The amounts of total and relative displacements were compared between the groups. Results: The total amount of displacement was 2.76 mm in group II, 2.81 mm in group III, and 2.83 mm in group I. The amount of relative displacement was 0.0078 mm in group II, 0.0093 mm in group III and 0.014 mm in group I. Conclusion: Our results suggested that all fixation systems enhance biomechanical stability significantly. Anterior column plate combined with quadrilateral area screws has quite comparable results to double column plates, they were superior to anterior column plate combined with posterior screws. Keywords: Acetabular, Anterior column and posterior hemi-transverse, Finite element analysis, Fixation system, Fracture